Pembinaan Moral Dan Perilaku Remaja Di Era Modern - Eko Nursalim (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
The issue of youth morality in Indonesia has become a profound social problem, with many deviant behaviors becoming increasingly prevalent among teenagers, such as gang fights, drug abuse, promiscuity, and bullying. These behaviors are rooted in various factors, both internal and external, that influence the moral development of adolescents. Dysfunctional families, inadequate religious education, negative peer influence, and increasingly unrestricted exposure to digital media are the main factors causing the degradation of adolescent morality. This problem is increasingly urgent given its significant impact on the future of Indonesia's younger generation.This study aims to examine in depth the factors causing the degradation of youth morals, its impacts, and the strategies that can be implemented by families, schools, communities, and the government. Using a qualitative approach with a library research method, this study analyzes various relevant literature to compile recommendations that can be applied in efforts to foster youth morals.The results of the study show that the main factors causing the degradation of youth morals include family dysfunction, lack of religious education, peer influence, and digital media. The impact is seen in individual psychological development, family conflicts, and an increase in social delinquency that disrupts social harmony. This study suggests several strategies for addressing these issues, including revitalizing the role of the family, strengthening character education in schools, improving digital literacy, providing guidance through religious and social activities, and cross-sector collaboration. This study contributes to the formulation of more holistic and community-based education and moral guidance policies.